2018
DOI: 10.1186/s12936-017-2151-y
|View full text |Cite
|
Sign up to set email alerts
|

Unclear association between levels of Plasmodium falciparum lactate dehydrogenase (PfLDH) in saliva of malaria patients and blood parasitaemia: diagnostic implications?

Abstract: BackgroundThe use of saliva in diagnosis of infectious diseases is an attractive alternative to procedures that involve blood drawing. It promises to reduce risks associated with accidental needle pricks and improve patient compliance particularly in malaria survey and drug efficacy studies. Quantification of parasitaemia is useful in establishing severity of disease and in assessing individual patient response to treatment. In current practice, microscopy is the recommended technique, despite its limitations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…A study showed that stored blood can lose antigen activity, and early lysis and protein coagulation can inhibit ow, thus in uencing the results of RDT-based malaria diagnosis [16]. Although this study and many others [23,24] clearly show the potential to use saliva as a non-invasive body uid for rapid diagnosis of malaria, there are still many challenges in establishing it as a reference.…”
Section: Discussionmentioning
confidence: 83%
“…A study showed that stored blood can lose antigen activity, and early lysis and protein coagulation can inhibit ow, thus in uencing the results of RDT-based malaria diagnosis [16]. Although this study and many others [23,24] clearly show the potential to use saliva as a non-invasive body uid for rapid diagnosis of malaria, there are still many challenges in establishing it as a reference.…”
Section: Discussionmentioning
confidence: 83%
“…However, the correlation co-efficient for the saliva supernatant pLDH results with respect to Microscopy results (ĸ = 0.21) was weaker than that reported by this study. In a similar study in Kenya [20], when the sensitivity of saliva pLDH was compared with blood film microscopy, saliva pLDH was found to be only 35% sensitive with weak positive correlation relative to the microscopy results.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the functionalization procedure of PIT can be carried out by a simple UV lamp in a few minutes, thus we anticipate that such an approach can be carried out in low resource settings which would be critical for many malaria diagnostic applications. Therefore, we foresee that our approach may provide a solution to the cold transport challenges common to the presently used immunochromatographic lateral flow assays [45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…The conventional serologic antibodybased rapid diagnostic tests rely upon the PfLDH detection in pretreated blood and offer rapid and cost-effective malaria diagnosis. However, the poor LOD as well as the transportation and storage difficulties of pre-functionalized devices in tropical environment make such tests unfit for early diagnosis and screening [45][46][47] . The ultrasensitive PEF-based device in combination with a unique functionalization procedure (PIT), which can be accomplished in a few minutes, results in an immunosensor suitable for detecting PfLDH at femtomolar level in the whole blood without any pretreatment and preconcentration steps.…”
mentioning
confidence: 99%